2018
DOI: 10.1002/cncy.22000
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry for histone H3G34W and H3K36M is highly specific for giant cell tumor of bone and chondroblastoma, respectively, in FNA and core needle biopsy

Abstract: H3G34W and H3K36M IHC is highly specific for GCT and chondroblastoma, respectively, among giant cell-rich bone tumors, and is useful for confirming the diagnosis in limited biopsies. The presence of alternate H3F3A mutations accounts for the H3G34W IHC negativity in a subset of GCT of bone cases. Cancer Cytopathol 2018. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…Nohr et al 16 . have suggested the diagnostic value of H3K36M and Schaefer et al 12 . have attempted H3K36M IHC in biopsy and give the conclusion that H3K36M IHC is a highly specific method in limited biopsies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nohr et al 16 . have suggested the diagnostic value of H3K36M and Schaefer et al 12 . have attempted H3K36M IHC in biopsy and give the conclusion that H3K36M IHC is a highly specific method in limited biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Behjati et al 6 has revealed the mutations on histone H3F3A and H3F3B are the driver mutations in the generation of CB and GCTB, respectively. Previous studies have reported that the H3K36M and H3G34W mutations distinguish CB cases and GCTB cases, both in immunohistochemistry (IHC) 12 and gene mutation analysis 13 . In our studies, we collected three suspected CB cases once treated as CB on admission, not obvious on diagnosis, and compared their results of immunohistochemistry and gene mutation analysis with the confirmed CB cases (Figs 2 and 4 E1-E4 and F).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the vast majority of CB harbour K36M substitutions resulting from H3F3B , or rarely H3F3A , mutations . Immunohistochemistry for monoclonal antibodies directed against the mutant histone H3.3 K36M proteins have been shown to be highly specific for the diagnosis of CB and are useful in challenging cases, particularly when the tumours are sampled with limited biopsy specimens …”
Section: Discussionmentioning
confidence: 99%
“…14,16,17 Immunohistochemistry for monoclonal antibodies directed against the mutant histone H3.3 K36M proteins have been shown to be highly specific for the diagnosis of CB and are useful in challenging cases, particularly when the tumours are sampled with limited biopsy specimens. 14,18 Clear cell chondrosarcoma is a rare, low-grade variant of chondrosarcoma that typically occurs in the third to fourth decades of life, and shows a predilection for the epiphyseal ends of long bones. The radiological findings overlap significantly with that of CB, as both may present as well-defined lytic lesions with a sclerotic rim often containing stippled calcific densities characteristic of cartilage matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to H3G34W, a histone H3K36M antibody has been developed; nuclear positivity is a strong predictor of underlying mutation. Both H3G34W and H3K36M have developed in parallel to become very useful diagnostic adjuncts, particularly in small biopsies and fine‐needle aspiration samples where the differential diagnosis among GCTB, CB, and aneurysmal bone cyst can be very challenging …”
Section: Single Nucleotide Variantsmentioning
confidence: 99%